Performansi peserta forum konsultasi publik BPS: pendekatan antropolinguistik - Cristy, Samuel Nugraha; Mahriyuni, Mahriyuni (Universitas Lampung, 2024)
The Public Consultation Forum (PCF) is one of the most important government surveys because it is a source of data that can help determine the level of welfare of every family in Indonesia. The data will be used as a benchmark for future government programs. This study aims to determine the form of participation by PCF participants focused on discovering performance patterns using anthropolinguistic approaches. This study used qualitative research methods. This research data is in the form of linguistic activities in PCF activities. The data was collected using recordings and notes. Oral data collected is transmitted into written language. Furthermore, the data were analyzed using domain, taxonomic and component analysis. The results showed that the performance of information provider participation in PCF activities was “to ask”, “answer”, “confirm”, and “fill in the documents”. There are 4 types of performance that occur in the process of these activities. The most dominant performance is the type of performance I.Keywords: Performance, Participation, BPS